Impact Of Information Tehcnology Implementation Operational Efficiency in UMKM - Purnama Sari, Diana; Anggraweni , Yessyca (Smart International Management Journal, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy with significant contributions to Gross Domestic Product (GDP) and employment absorption. In today's digital era, the application of information technology (IT) is a potential solution to overcome these challenges. However, the implementation of IT in the MSME sector still faces various obstacles, especially in terms of finance and limited technical capabilities. This study uses a descriptive-correlational survey design to show how information technology is used in MSMEs and measures the correlation or relationship between IT variables and operational efficiency variables. The data are collected and analysed qualitatively and statistically. The results of the study show that the use of IT has a positive and significant impact on the operational efficiency of MSMEs, particularly in saving time, reducing operational costs, and increasing productivity. In addition, the positive correlation between IT implementation and operating efficiency shows that the higher the use, the greater the impact on improving MSME performance. Comparative studies between sectors or regions can enrich insights into the effectiveness of IT and provide more specific recommendations to support sustainable digitalisation in this sector.